EFFECT OF MENOPAUSE ON SERUM HDL-CHOLESTEROL LEVEL - Sultan, Norin; Nawaz, Muhammad; Sultan, Ambreen; Fayaz, Muhammad; Baseer, Abdul (Journal of Ayub Medical College Abbottabad, 2003)
Background: There is a marked difference in the risk of coronary heart disease between men and women of reproductive age but this gap closes with advancing age. It seems likely that some factors of reproductive physiology are responsible for this. The present study was designed to evaluate the difference in HDL Cholesterol level in premenopausal and postmenopausal women in relation with change of estradiol level. Methods: Fifty premenopausal and 50 postmenopausal women were included in the study. Estradiol was estimated by radioimmuoassay while HDL-C was estimated by Kit method. Results: There was a significant (p<0.01) decrease in the HDL-C level of the postmenopausal women (46.72±1.009) as compared with premenopausal women (63.68±1.78). Conclusion: HDL-C is an independent risk factor for coronary heart disease. This study favours the view that decrease in estradiol level and associated decrease in HDL-C seen in postmenopausal women may be responsible for the increased risk of coronary heart disease after menopause. Keywords: Menopause; HDL-Cholesterol; Risk factor; Coronary Heart Disease